Analisis Karakteristik Mahasiswa Sebagai Acuan Dalam Merumuskan Strategi Pembelajaran Di Program Studi Pendidikan Matematika Stkip Abdi Wacana Wamena - Borean, Sutarman; Napitupulu, Citra Ratna; Sinambela, Mindo Hotmaida; Rumpasium, Christine Mersi (Neolectura, 2024)
This study aims to analyze the characteristics of students in the Mathematics Education Study Program at STKIP Abdi Wacana Wamena as a basis for formulating appropriate learning strategies to optimize learning outcomes. The research uses a mixed-method approach by adapting the convergent parallel design model. The researcher conducts both quantitative and qualitative research concurrently, or within the same phase of the study, and then combines the results during the overall interpretation. The data collection techniques used in this research include questionnaires, interviews, observations, and documentation. The collected data is then processed and analyzed descriptively. The results of the study show that the characteristics of students in the Mathematics Education Study Program at STKIP Abdi Wacana are highly heterogeneous. To accommodate the diversity of student characteristics, various supporting facilities, such as learning infrastructure, are required. The regular use of diverse learning resources, including people, information, software, equipment, models, methods, and environments, will help students build a deeper understanding of their field of study. In this context, lecturers can develop various learning resources that can facilitate the learning process for students with diverse characteristics, thereby optimizing learning outcomes.